Reducing urban heat island effects: A systematic review to achieve energy consumption balance - Shahmohamadi, P.; Che-Ani, A.I.; Ramly, A.; Maulud, K.N.A.; Mohd-Nor, M.F.I. (Academic Journals, 2010)
Considering the current energy consumption worldwide, it has become increasingly important to study the effects of urban heat island on energy consumption in order to improve the environment. This paper investigates the impact of Urban Heat Island (UHI) on energy consumption and also determines which factors can directly affect energy use in the city. The UHI current knowledge and literature are reviewed, as well as how UHI can affect energy consumption. This paper explores literally the conceptual framework of confliction between population and urban structure, which produce UHI intensity and affected energy consumption balance. It is then discussed how these two factors can be affected and gives implication to the city and then, focuses on whether actions should be taken for balancing adaptation and mitigation UHI effects. It will be concluded by making the three important strategies to minimise the impact of UHI on energy consumption: providing an appropriate landscape, using appropriate materials on external surfaces of buildings and urban areas and promoting natural ventilation.